"For better for what? some psychosocial factors in marital violence. " (2001)
"This study examined the effects of self-esteem, socioeconomic status and age on marital violence. Marital violence is a phenomenon that is found to be pervasive in all cultures of the world, people go to the Altar to take marital vow, to love, cherish and keep one another for better for worse, in sickness and in health. However, the situation in most homes is afar cry from the vow willingly taken by couples, rather, homes are riddled with physical, psychological and other forms of violence. Results from this study revealed that self-esteem has no direct effect on initiating and maintaining marital violence, while socioeconomic status does; also, no relationship was observed between age and marital violence. Recommendation was made on approach that may be adopted to reduce incidence of marital violence. "